2022
DOI: 10.1371/journal.pone.0276381
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19 knowledge among Ghanaians: A national survey

Abstract: Background Adequate knowledge about COVID-19 in a population may be relevant in the fight to control its spread among the populace. Thus, the aim of this study was to assess the factors associated with real knowledge of COVID-19 among Ghanaians to promote effective dissemination of appropriate information aimed at containing the spread. Methods A cross-sectional online survey and computer assisted telephone interviews (CATI) was conducted among Ghanaians aged 18 years and above across the 260 districts of Gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Factors such as age, type of disability, level of education and income were found to influence respondents’ knowledge of Covid-19. This finding is similar to a study in Ghana by Kwabla et al which also identified age and education as positive influencing factors on people’s knowledge of covid-19 [ 17 ]. The type of impairment was also found to influence the respondent’s level of knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Factors such as age, type of disability, level of education and income were found to influence respondents’ knowledge of Covid-19. This finding is similar to a study in Ghana by Kwabla et al which also identified age and education as positive influencing factors on people’s knowledge of covid-19 [ 17 ]. The type of impairment was also found to influence the respondent’s level of knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…of this study is similar to findings from studies with the general public [17][18][19], which reported a higher level of knowledge on Covid-19. Our study revealed an average 70.00% knowledge score among respondents.…”
Section: Plos Global Public Healthsupporting
confidence: 90%
See 2 more Smart Citations
“…A systematic review reported that the education, income, and age were among the significant factors associated with poor knowledge regarding the pandemic of COVID-19 [ 33 ]. Another study found that Ghanaians’ knowledge about COVID-19 was significantly affected by their age and education [ 34 ]. Ethiopian healthcare professionals’ knowledge about COVID-19 was also affected by their age, education, and income [ 35 ].…”
Section: Discussionmentioning
confidence: 99%